STUDY OF THE EFFECT ON THE NATURAL CHARACTERISTICS OF FIBER IN THE PROCESS OF APPLICATION OF COTTON PROCESSING TECHNOLOGY - SH.SH.ISAEV; ERGASHEV YU; N.M.ORIPOV; I. XAKIMOV (International Journal of Innovations in Engineering Research and Technology, 2021)
The article examines the structures of cleaners describing the separation of large and small weed impurities from the cotton mass, will determine the parameters for calculating the cleaning effect of having an elastic bond with cotton.